Dehydrogenative Silylation of Alcohols Under Pd‐Nanoparticle Catalysis. Issue 3 (12th December 2018) - Pramanik, Suman; Fernandes, Anthony; Liautard, Virginie; Pucheault, Mathieu; Robert, Frederic; Landais, Yannick
Abstract: Pd‐nanoparticle‐catalyzed dehydrogenative coupling between various hydrosilanes and alcohols was shown to provide silyl ethers in good and reproducible yields. The synthetic methodology is effective for a wide range of simple and bulky silanes and secondary alcohols, while keeping various other functional groups intact. The procedure also exhibits high selectivity for the silylation of primary versus secondary alcohols in 1, 2‐diols, and allows the successive silylation of alkynols and hydrogenation of the triple bond to afford Z ‐alkenols in good yields. Abstract : Pd‐nanoparticle‐catalyzed dehydrogenative coupling between hydrosilanes and alcohols to give silyl ethers is described. High selectivity for the silylation of primary versus secondary and secondary versus tertiary alcohols in 1, 2‐diols is observed. Tandem silylation/hydrogenation of the triple bond of alkynols to afford Z ‐alkenols has also been achieved.